2007
DOI: 10.1007/s11250-007-9057-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute coliform mastitis in buffaloes (Bubalus bubalis): Clinical findings and treatment outcomes

Abstract: This report was delineated to study the clinical, bacteriological and therapeutic aspects concerned with acute coliform mastitis in buffaloes. Bacteriological examination of 80 quarter milk samples obtained aseptically from 56 buffaloes with acute mastitis revealed that coliform bacteria was the most common pathogen (45 cases) followed by Staphylococcus aureus (seven cases) then Streptococcus uberis (three cases), and Streptococcus agalactiae (one case). Clinically, hotness, swelling and painful reaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Another interesting observation was that more than one pathogen had been found in some mastitis sample. Similar phenomena have been also reported by the others, Sabry A groups showed that mixed infection by Klebsiella pneumoniae and E.coli was more prevalent than single infection on both animal and quarter level [25],…”
Section: Discussionsupporting
confidence: 87%
“…Another interesting observation was that more than one pathogen had been found in some mastitis sample. Similar phenomena have been also reported by the others, Sabry A groups showed that mixed infection by Klebsiella pneumoniae and E.coli was more prevalent than single infection on both animal and quarter level [25],…”
Section: Discussionsupporting
confidence: 87%
“…Prevalence of coliform infections (Table 2) disagreed with Hawari and Al-Dabbas [52] who detected coliforms in the milk of 31.9% of the mastitic quarters. On the other side, El-Khodery and Osman [53] detected coliforms in 80.36% of the affected buffaloes, but Sayed [54] recorded lower coliform prevalence (21.78%) in the examined milk samples. Escherichia coli was isolated form 7.7% quarter milk samples which is lower than that reported by Verma et al [55] (21.28%).…”
Section: Discussionmentioning
confidence: 98%
“…2 Bacteria isolated with greatest frequency are Staphylococcus aureus, Staphylococcus spp., Bacillus spp., Corynebacterium spp., Escherichia coli, Streptococcus spp., Pseudomonas spp., and Klebsiella spp. 7,9,13 Besides causing mastitis, the genera Staphylococcus are the etiologic agents responsible for approximately 45% of toxin infections worldwide. Contamination can occur by strains of environmental or human origin during the stages of food production or storage; in favorable temperature conditions, the microorganism grows and may produce toxins.…”
mentioning
confidence: 99%
“…The most important effect is related to economic losses due to decrease in milk yield. 7 Among the microorganisms responsible for mastitis, bacteria are implicated as the principal etiologic agents. 2 Bacteria isolated with greatest frequency are Staphylococcus aureus, Staphylococcus spp., Bacillus spp., Corynebacterium spp., Escherichia coli, Streptococcus spp., Pseudomonas spp., and Klebsiella spp.…”
mentioning
confidence: 99%